1981
DOI: 10.1111/j.1346-8138.1981.tb02541.x
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Paget's Disease

Abstract: A case of axillary Paget's disease in a female was presented. Histopathological study revealed various types of apocrine poral duct tumors showing benignancy, premalignancy or malignancy, and Paget's cells in the epidermis as well as in the latter lesions. Relationship between Paget's cell and the malignant cell was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Axillary location of EMPD is very rare. A review of the literature revealed only 23 cases reported so far, the majority in Japanese population 48–64 (Table 1). Of these, 10 cases had isolated axillary involvement, while 13 demonstrated simultaneous axillary and genital disease (the so‐called triple EMPD).…”
Section: Discussionmentioning
confidence: 99%
“…Axillary location of EMPD is very rare. A review of the literature revealed only 23 cases reported so far, the majority in Japanese population 48–64 (Table 1). Of these, 10 cases had isolated axillary involvement, while 13 demonstrated simultaneous axillary and genital disease (the so‐called triple EMPD).…”
Section: Discussionmentioning
confidence: 99%
“…Extramammary Paget's disease of the skin is an un common pathological entity associated with the presence of a carcinoma, usually of apocrine type in 50-80% of the cases. The anogenital region is typically involved, but the disease has been reported to occur in other areas including the axilla [1], eyelid [2] and external auditory canal [3], Paget's disease of the genital mucosa in association with carcinoma of the lower urinary tract is well documented. However, to our knowledge, only 4 cases of intra-epithelial spread onto the glans penis from transitional cell car cinoma (TCC) of the bladder have been reported in the literature [4][5][6][7], a further associated with primary carci noma of the prostate [8] and another with adenocarcino ma of a peri-urethral gland [9], We present a further case of Paget's disease of the glans penis with an underlying TCC of both bladder and urethra and discuss the clinical significance of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…EMPD can occur in various parts of the body, especially in those where the skin is rich in apocrine and eccrine glands [3, 4]. The most common treatment is surgical excision but the disease tends to recur very easily, and in a certain percentage of cases (12%) it is associated with a primary malignancy [2].…”
Section: Introductionmentioning
confidence: 99%